Analysis of nursing students' perspective regarding patient care with suspected sepsis (Research, Society and Development, 2023)
Objective: To evaluate the perception of nursing students regarding the recognition of sepsis. Methods: This is a descriptive research study, with a qualitative approach, conducted at the University Center in Curitiba. Thirty nursing students from the 7th period onward participated during the month of June 2023. Sociodemographic and semi-structured questionnaires based on a case study were applied. Results: Most students had no experience in attending to patients with suspected sepsis. Facilitating aspects were identified, such as observation on alteration and dysfunctions, and difficulties related to the prescription of nursing care. Conclusion: Limited knowledge about sepsis was evidenced among the students. In this sense, it is essential to expand teaching on sepsis in nursing education to better prepare future professionals and ensure quality patient care.